Business Survivability: Social Media as a Channel in the Pandemic Era - Miftha Pratiwi (Ikatan Sarjana Komunikasi Indonesia, 2021)
Almost this past one-year Indonesia has been undergoing global crisis due to COVID-19 pandemic. The weakening of economic sector is caused by the restriction of activity as one form of the supports for the Government in applying health protocol. Many companies of various fields are unable to survive because of undergoing economic contraction. While there are so many companies are having economic contraction, YLEO Indonesia strives. According to one of the distributors, who gains a status as a diamond leader, the income of YLEO increases to 40% during the pandemic. This success is certainly not apart from the role of strategic communication conducted by the company. Moreover, if the company uses social media as one means or channel of communication in conveying education, promotion and interaction with its audience. This research aims at understanding the utilization of social media as a means of communication adopted which supports the business activity of YLEO. The method employed is qualitative descriptive in the form of in-depth interviews as the data collection technique, and content analysis. The summary of this research is the management and utilization of social media as important parts of the company because they are able to encourage the involvement of the audience in various activities in order to further know and understand the expectation and message relevancy which are conveyed to the audience.